2019
DOI: 10.1016/j.conctc.2019.100412
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of smoking cessation with varenicline plus counselling for e-cigarettes users (VAREVAPE): A protocol for a randomized controlled trial

Abstract: Tobacco smoking is a global pandemic that poses substantial health burdens and costs. With nearly six million deaths annually, smoking is the single most important cause of avoidable premature mortality in the world, mainly from lung cancer, coronary heart disease, chronic obstructive pulmonary disease and stroke. Smoking is a very difficult addiction to break, even for those with a strong desire to quit. Electronic cigarettes are an attractive long-term alternative source of nicotine to conventional cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Study results complement and are largely consistent with the handful of clinical trials assessing causal effects of e-cigarettes on smoking cessation. 6 , 7 , 8 , 9 , 10 , 11 , 12 Study results are also consistent with a handful of population-based studies that have shown an association between e-cigarete use and smoking cessation, 27 , 28 , 29 as well a number of studies that have shown that frequency of use is an important determinant in this association. 30 , 31 , 32 As a naturalistic randomized trial, the current study was aimed primarily to examine the uptake of and outcomes from e-cigarettes, across a broad range of smokers given minimal guidance or instructions on use.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Study results complement and are largely consistent with the handful of clinical trials assessing causal effects of e-cigarettes on smoking cessation. 6 , 7 , 8 , 9 , 10 , 11 , 12 Study results are also consistent with a handful of population-based studies that have shown an association between e-cigarete use and smoking cessation, 27 , 28 , 29 as well a number of studies that have shown that frequency of use is an important determinant in this association. 30 , 31 , 32 As a naturalistic randomized trial, the current study was aimed primarily to examine the uptake of and outcomes from e-cigarettes, across a broad range of smokers given minimal guidance or instructions on use.…”
Section: Discussionsupporting
confidence: 85%
“…Systematic reviews 1 , 2 and meta-analyses 3 , 4 , 5 suggest a beneficial role for electronic (e-)cigarettes to promote smoking cessation. However, the individual trials that form the basis for this conclusion 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 are few in number and primarily come from outside the United States. Randomized trials are challenging to conduct within the U.S. given the regulatory environment that makes it difficult to assess (or claim) a therapeutic purpose for e-cigarettes, as would be the case for any study that is designed explicitly for this intent.…”
Section: Introductionmentioning
confidence: 99%
“…The current lack of available evidence describing the use of pharmacotherapy and other interventions to support vaping cessation has been identified as a knowledge gap in the literature. 35 Similarly, while previous CADTH reports have sought evidence describing interventions to support smoking cessation [36][37][38][39][40] -including 1 describing the use of ENDS products to support smoking cessation 41 -only 1 recent CADTH report sought evidence describing the clinical effectiveness of nicotine replacement therapy for vaping cessation in adults, but no relevant studies were identified. 42 This lack of clinical evidence is consistent with the findings of the current report, which has identified a lack of available guidelines informing the use of any pharmacological interventions to support vaping cessation.…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 99%
“…15 Notably, 1 published protocol was identified describing initiation of a randomized controlled trial to evaluate the efficacy of a combined behavioural and pharmacological intervention using varenicline and counselling to support vaping cessation. 35 Continued research in this area will provide evidence to inform recommendations regarding vaping cessation.…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 99%